2016
DOI: 10.4103/2321-0656.164795
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Tribes of India: A literature review

Abstract: Diabetes mellitus (DM), commonly regarded as a lifestyle disease, used to be a disease of affluent societies in the days of yore. However, now it has encroached into the rural and tribal communities as well. This narrative review provides us with an understanding of the epidemiology of diabetes burden in tribes of India. Around 15% of the country′s area is covered by tribals and it constitutes ~8.6% (i. e., ~104 million) of India′s total population. Prevalence of diabetes in tribal areas ranges from around 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This is consistent with a study conducted by Tamornpark et al 27 , which reported that older Lahu, Yao, Karen, and Lisu people were more likely to suffer from T2DM than older Akha people. A literature review identified risk factors for T2DM in different tribes in India, and some tribes were found to be at a significantly greater risk of suffering from T2DM than other tribes 28 . This might be related to genetic, culinary tradition and lifestyle differences among the tribes.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a study conducted by Tamornpark et al 27 , which reported that older Lahu, Yao, Karen, and Lisu people were more likely to suffer from T2DM than older Akha people. A literature review identified risk factors for T2DM in different tribes in India, and some tribes were found to be at a significantly greater risk of suffering from T2DM than other tribes 28 . This might be related to genetic, culinary tradition and lifestyle differences among the tribes.…”
Section: Discussionmentioning
confidence: 99%
“…The studies have suggested that hypertension is widespread or even on the rise in tribal populations, with 26% of the individuals there having hypertension ( 9 ). As a result of blood glucose levels also being elevated, 1% to 10% of the tribal population is diabetic ( 10 ). Studies have also been conducted to determine the prevalence of metabolic syndrome in different Indian tribes, and the results show alarming numbers.…”
Section: Metabolic Syndrome In Tribesmentioning
confidence: 99%
“…Once regarded as lifestyle diseases with higher prevalence in affluent households, NCDs are increasingly reported from rural communities [ 6 ]. However, due to poor data quality from routine health services and limited research among hard-to-reach populations in forested areas with tribal and remote rural communities, their prevalence and risk factors have not been well characterized in public health literature.…”
Section: Introductionmentioning
confidence: 99%
“…There are scarce efforts at characterizing the risk factors and epidemiology of NCDs, particularly among remote rural and tribal populations, due to geographical challenges in organizing surveys and limited research infrastructure in forested and remote areas. Although several studies have examined the prevalence of hypertension (HTN) and Diabetes among tribal communities, data on the prevalence of these conditions among tribal and non-tribal communities residing in and around the forested area remains unavailable [6,[11][12][13][14][15]. Although several meta-analyses have been conducted on diabetes and hypertension among tribal populations, none have been conducted using a systematic sampling effort among tribal populations in southern Karnataka [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%